(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
This article discusses some reflections developed by Gérard Genette with respect to the filmic examples in Métalepse and tries to pursue the study of this figure within the framework of fiction theories by focusing on certain films released in the last decade. The article also shows how the study of metalepsis can be important in order to address contemporary movies pre- senting complex self-reflexive strategies. Furthermore, it gives account of the particular way in which Genette deals with cinema and suggests some other possible theoretical develop- ments, considering in particular the theories about filmic enunciation. Finally, the paper dis- cusses some problems concerning Genette’s idea of “diegesis” when it is applied to cinema and analyses the transgression of narrative levels in a voice-over film – in this case Stranger than Fiction (Marc Forster, 2006), which provides a particularly interesting example in order to test some of Genette’s remarks.